Analisis Nilai-Nilai Kearifan Lokal Yang Terdapat Dalam Tradisi Tepuk Tepung Tawar Di Desa Sungai Selari Kecamatan Bukit Batu Kabupaten Bengkalis - Iqbal chozanatuha; Hambali '; Gimin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: the background of this research by one of the traditions of the Malay culture fresh flour, which is loaded and the rich values of local wisdom contained in it, moral values, attitudes and philosophies of life, so the authors take the title “Analysis of the values of local wisdom embodied in the tradition fresh flour in the village of sungai selari subdistrict bukit batu district bengkalis”. Formulation of the problem in this research are anyvalues of local wisdom contained in the tradition of fresh flour in the village of sungai selari subdistrict bukit batu district bengkalis? The purpose of this research is to find out what values of local wisdom contained in the tradition of fresh flour in the village of sungai selari subdistrict bukit batu district bengkalis. This study population is rural river Selari totaling 2205 people. Purposive sampling technique with a sampling of 50 people. Data were collected through observation, questionnaires, interviews, documentation, and study the literature, in analyzing data using quanlitative descriptive analysis. Formulation of hypothesis that “there are Analysis of the values of local wisdom embodied in the tradition fresh flour in the village of sungai selari subdistrict bukit batu district bengkalis” is in the category of “be found”.50% respondent answered strongly associated by 17,48%, amounting to 51,22% associated answered, answered by 24,52% less related and unrelated answer by 5,04%. Keywords:local wisdom, tradition fresh flour